An invisible villain: high perceived stress, its associated factors, and possible consequences in a population-based survey in southern Brazil - Lauro Miranda Demenech; Sara S. Fernandes; Renata Gomes Paulitsch; Samuel C. Dumith (Trends in Psychiatry and Psychotherapy, 2022)
Abstract Introduction Much of the evidence on the relationship between stress, lifestyle, and other physical and mental health outcomes comes from studies conducted in high-income countries. There is therefore a need for research among populations in low and middle-income settings. Objectives To measure stress levels and identify factors associated with a high stress level and its consequences for health. Methods This was a population-based cross-sectional study carried out in 2016 with adults aged 18 years or older in a municipality in southern Brazil. A two-stage sampling strategy based on census tracts was used. Stress levels were measured with the Perceived Stress Scale (PSS-14) and classified into quartiles. The impact of the highest stress levelon each outcome was assessed with etiologic fractions (EF). Results The most stressed groups were: females (PR = 1.51, 95%CI 1.25-1.81), younger people (PR = 1.76, 95%CI 1.26-2.46), middle-aged individuals (PR = 1.60, 95%CI 1.17-2.19), those with lower schooling (PR = 1.56, 95%CI 1.20-2.02), the physically inactive (PR = 1.51, 95%CI 1.20-1.91), people who spent three or more hours watching television per day (PR = 1.29, 95%CI 1.12-1.50), and those with food insecurity (PR = 1.44, 95%CI 1.19-175). Possible consequences of high stress level were regular or poor self-perception of health (EF = 29.6%), poor or very poor sleep quality (EF = 17.3%), lower quality of life (EF = 45.6%), sadness (EF = 24.2%), and depressive symptoms (EF = 35.8%). Conclusions Stress plays an important role in several domains of health. Both public policies that target reduction of inequalities and specific stress-management interventions can reduce stress levels in populations, thereby decreasing the burden of other negative physical and mental health outcomes related to stress.